2008
DOI: 10.21273/hortsci.43.5.1344
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicinoids Content in Habanero Pepper (Capsicum chinense Jacq.): Hottest Known Cultivars

Abstract: The aim of this study was to determine the pungency level of different accessions of Habanero peppers. The high-performance liquid chromatography (HPLC) technique was used to evaluate the content of total capsaicinoids in the whole fruit, placenta, and pericarp of 18 accessions of Habanero pepper from the germplasm bank of the Capsicum chinense species maintained in the Scientific Research Center of Yucatan [Centro de Investigación Científica de Yucatán (CICY)]. Thirteen of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
49
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 32 publications
3
49
0
2
Order By: Relevance
“…Capsaicin contents in pods (Fig. 3(A)) from plants cultured on the different nitrate concentrations were in the range previously reported for plants from the same geographical area 11, 18. Interestingly, total capsaicinoid content in placentas (Fig.…”
Section: Resultssupporting
confidence: 79%
“…Capsaicin contents in pods (Fig. 3(A)) from plants cultured on the different nitrate concentrations were in the range previously reported for plants from the same geographical area 11, 18. Interestingly, total capsaicinoid content in placentas (Fig.…”
Section: Resultssupporting
confidence: 79%
“…The present study identified 17 genotypes from C . chinense group with more than 0.9 million SHU which is distinctly higher than the previously reported pungency of Habanero [47,48,49]. Although, Bhut jolokia ( C .…”
Section: Discussionmentioning
confidence: 61%
“…Of the 20 accessions with the highest capsaicinoid contents, eight were C. frutescens , seven were C. chinense , and five accessions were C. annuum . The three most pungent accessions, ‘Habanero’, ‘9007’ and ‘Spain 5’, were all accessions of C. chinense , which is well known for its pungency (Bosland and Baral, ; Bosland et al ., ; Canto‐Flick et al ., ).…”
Section: Resultsmentioning
confidence: 97%